Pentingnya Pencegahan Stunting Dalam Rangka Pertumbuhan dan Perkembangan Anak Yang Optimal - Hardono, Joko; Lestari, Sri (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
From the Tangerang Regency Government website reported that babies aged 0-15 months in Pasar Kemis District, Tangerang Regency, in 2022 recorded as 18,919 babies, 86 under stunting. This research aims to analyze the factors that contribute to the incidence of stunting, provide outreach on how to handle and efforts to prevent stunting in toddlers. This research used a cross-sectional study design and collected data from 25 mothers of toddlers in Gelam Jaya, Pasar Kemis District, Tangerang Regency. Respondents were selected using stratified random sampling. Data was collected through interviews using collected questionnaires and anthropometric measurements on toddlers. Data analysis was carried out using descriptive statistical methods. Posyandu activities which are routinely carried out by PKK Mobilization Team in collaboration with the Kotabumi Community Health Center are responded by mothers’s toddlers with passive participation that is not accompanied by a deep awareness of the importance of the program. With the existence of an innovation program through seminar activities and a “dapur dasyat” program where mothers are directly involved in cooking healthy food for toddlers, it is able to raise mothers' awareness of the dangers of stunting, understanding how to prevent stunting and the importance of baby's nutrition to avoid stunting. More over that they also realized was that nutritious food for toddlers did not have to be expensive and could be made by themselves.